The effects of mindfulness-based stress reduction therapy on psychopathology symptoms and stress response in patients with multiple sclerosis: Short communication - Arman Eftekhari (Chronic Diseases Journal)
BACKGROUND: Multiple sclerosis (MS) is a chronic inflammatory condition that affects the central nervous system (CNS). The purpose of this study was to examine how a mindfulness-based stress reduction (MBSR) intervention impacted psychopathology symptoms and stress responses in patients with MS.